Horizontal Parallelism in The Whispering of the Eyelids by Mikhail Naima Study in Selected Models - Mohammed, Qasim; Ibrahim, Ramadhan (Humanities Journal of University of Zakho, 2021)
The research deals with phenomenon of horizontal parallelism in the poetry of Mikhail naima in his collection whispers of the eyes, due to the aesthetic value of horizontal parallelism in the consideerd an important teibutary tributary of rhythm on the hand . and its direct relationship to the semantic fromation on the other hand. It was learned that although the word parallel was not used in its text , it come within terms that fall this concept, such as : returning the disability to the chest . the descriptive approach writing this research by examining phenomenon in the poetry of Mikhail naima, as well as the aesthetic approach, and we benefited from was presented by the Arabic rhetoric of concepts that illuminated the aesthetic and semantic side parallelism, the research concluded that the poet Mikhail Naima , he emlloys horizontal parallesim in his vertical poems , and this parallelism was evident in many poems in the eyelid whisper, the horizontal results from the components of the components of the linguistic element represented by sounds, vocabulary or structures that are repeated witgin the space of one stanza or at tge level of one verse of the pome , in this research, I will discuss the horizontal parallelism , which was a prominent feature in the framework of the sungle verse of the poems of the diwan, these types are originally old terms mentioned in the books of the rhetoricians , previously or wrote literature and performances as well, including the response to the impotence on the chest and the epilepsy .